2019
DOI: 10.32394/rpzh.2019.0061
|View full text |Cite
|
Sign up to set email alerts
|

Role of diet-related factors in cerebral aneurysm formation and rupture

Abstract: Cerebral aneurysms (CAs) are dilations of the wall of an artery in the brain filled with blood. The prevalence of unrupted CA in general population is estimated at approximately 3%. Ruptured aneurysms are the cause of 85% of spontaneous subarachnoid hemorrhage (SAH) cases. The formation of cerebral aneurysms results from various factors, including chronic inflammation, hemodynamic stress and vascular wall remodeling. Reactive oxygen species may induce the endothelial dysfunction possibly through the activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…According to studies, the recurrence rate of intracranial aneurysm after endovascular interventional therapy is up to 20.8%–36%, and patients who have risk factors including smoking, alcoholism, hypertension, diabetes mellitus, and hyperlipidemia often face risks of multiple or postoperative recurrence [ 14 , 15 ]. The related factors of intracranial aneurysm rupture are not only bound up with the size and location of the intracranial aneurysm but also strongly bound up with patients' self-protection, emotional management, blood pressure control, medication compliance, and changes of bad living habits [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to studies, the recurrence rate of intracranial aneurysm after endovascular interventional therapy is up to 20.8%–36%, and patients who have risk factors including smoking, alcoholism, hypertension, diabetes mellitus, and hyperlipidemia often face risks of multiple or postoperative recurrence [ 14 , 15 ]. The related factors of intracranial aneurysm rupture are not only bound up with the size and location of the intracranial aneurysm but also strongly bound up with patients' self-protection, emotional management, blood pressure control, medication compliance, and changes of bad living habits [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these recent discoveries about HT, it has also been described that the Mediterranean diet can positively impact the cardiovascular system thanks to its antioxidant effects [ 70 ]. Precisely, two studies have tested the risk of abdominal aortic and cerebral aneurysms in relation to Mediterranean diet adherence [ 71 , 72 ]. They have been conducted on a very large sample and have demonstrated that a Mediterranean diet based on a high consumption of fruits, vegetables, wholegrains, legumes, nuts, fermented dairy products, fish, and olive and/or rapeseed oil; moderate consumption of alcohol; and low consumption of processed and unprocessed red meat may represent a positive factor for the prevention of two forms of aneurysm [ 71 , 72 ].…”
Section: From the Experimental Aspects To Translational Medicine: Ant...mentioning
confidence: 99%
“…The data obtained have demonstrated the HT capacity of selectively inhibiting the protein glycation reaction in human insulin, and of counteracting the AGE-induced cytotoxicity by acting on sirtuins levels and oxidative stress, as well as on inflammatory response [62] Consistent of these recent discoveries on HT, it has been also reported that Mediterranean diet may positively impact the cardiovascular system thanks to its antioxidant effects [63]. Precisely, two studies have tested the risk of abdominal aortic and cerebral aneurysms in relation to Mediterranean diet adherence [64,65]. They have been conducted on very large sample size and have demonstrated that a Mediterranean diet based on high consumption of fruits, vegetables, wholegrains, legumes, nuts, fermented dairy products, fish, use of olive and/or rapeseed oil, moderate consumption of alcohol, and low consumption of processed and unprocessed red meat, may represent a positive factor for the prevention of two forms of aneurysm [64,65].…”
Section: Natural Compounds and Mediterranean Dietmentioning
confidence: 99%
“…Precisely, two studies have tested the risk of abdominal aortic and cerebral aneurysms in relation to Mediterranean diet adherence [64,65]. They have been conducted on very large sample size and have demonstrated that a Mediterranean diet based on high consumption of fruits, vegetables, wholegrains, legumes, nuts, fermented dairy products, fish, use of olive and/or rapeseed oil, moderate consumption of alcohol, and low consumption of processed and unprocessed red meat, may represent a positive factor for the prevention of two forms of aneurysm [64,65]. No studies there are about AsAA and Mediterranean diet until now.…”
Section: Natural Compounds and Mediterranean Dietmentioning
confidence: 99%